The Effect of A Blended Learning Project Based Learning Model on Scientific Attitudes and Science Learning Outcomes of Grade V SD Students - Tika, I Nyoman; Agustiana, I Gusti Ayu Tri (Jurnal Ilmiah Sekolah Dasar, 2021)
The Covid -19 pandemic demands learning using an online system. This study aims to describe the effect of project-based learning model assisted by blended learning on scientific attitudes and science learning outcomes. The study population was all fourth grade elementary school students in the Banyuning Cluster, Buleleng District, 2020/2021 academic year, with 8 classes with a total of 184 students. The research samples were SDN 1 Banyuning with 31 students as the experimental group and SDN 8 Banyuning with 30 students as the control group; determined by random sampling technique. Sampling using random sampling technique. The design uses Post test Only Control Group Design. Scientific Attitude data were collected using a questionnaire and science learning outcomes were collected through objective tests. Data were analyzed through descriptive statistics and the Manova SPSS-17 test. The results show that (1) there is a significant difference in scientific attitudes between students who follow the project-based learning model assisted by blended learning and students who follow the conventional learning model, as evidenced by having an F value of 471.8 with a significance value of 0.000 or less than 0. ,05. (2) there is a significant difference in science learning outcomes between students who follow the project-based learning model assisted by blended learning and students who take conventional learning as evidenced by the science learning outcomes that have an F value of 3.69 with a significance value of 0.000 or less than 0 ,05. This shows that the F value in the dependent variable of science learning outcomes is significant (3) there are differences in scientific attitudes and science learning outcomes simultaneously between students who follow the project-based learning model assisted by blended learning and students who follow the conventional learning model. a significance level of 0.05 resulted in a p < 0.05.